2005
DOI: 10.1002/humu.20205
|View full text |Cite
|
Sign up to set email alerts
|

Identification of mutations in the GNPTA (MGC4170) gene coding for GlcNAc-phosphotransferase α/β subunits in Korean patients with mucolipidosis type II or type IIIA

Abstract: Mucolipidosis types II and III are autosomal recessive inherited diseases caused by a deficiency in the lysosomal enzyme N-acetylglucosamine-1 phosphotransferase (GlcNAc-phosphotransferase), which adds phosphate to function as a recognition marker for the uptake and transport of lysosomal enzymes. We investigated mutations in the GNPTA (MGC4170) gene, which codes for the alpha/beta subunits of phosphotransferase, and in the GNPTAG gene, which codes for its gamma subunits in five Korean patients with mucolipido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
51
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 18 publications
6
51
1
1
Order By: Relevance
“…Eight of 25 ML II patients have this mutation homozygously. According to previous reports, this mutation was only found in two Korean cases 11 and in one case of Irish/Scottish origin. 13 This mutation seems to be common in eastern Asia, including Japan.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…Eight of 25 ML II patients have this mutation homozygously. According to previous reports, this mutation was only found in two Korean cases 11 and in one case of Irish/Scottish origin. 13 This mutation seems to be common in eastern Asia, including Japan.…”
Section: Discussionmentioning
confidence: 79%
“…These include 14 new mutations and four previously detected mutations. All four known mutations were reported by a Korean group 11 and one, p.R1189X, was also reported by an Israeli group in a patient of Irish/Scottish origin. 13 The most frequent mutation was the nonsense mutation p.R1189X (c.3565C4T) and its allele frequency was 33/80 (¼41.25%) in the analyzed alleles of all ML II and III patients.…”
Section: Mutations In ML Ii Alpha/beta and Iii Alpha/beta Patientsmentioning
confidence: 74%
See 2 more Smart Citations
“…Recently, we identified a novel gene, GNPTA, encoding a protein of 1,256 amino acids with two putative transmembrane domains and a complex module structure which is required for proper phosphotransferase activity [Tiede et al, 2005a]. Defects in GNPTA result in mucolipidosis type II (ML II, I-cell disease; MIM# 252500) [Paik et al, 2005;Tiede et al, 2005a;Kudo et al, 2006] whereas mutations in GNPTG were found in ML III patients (pseudo Hurler-polydystrophy; MIM# 252600) [Raas-Rothschild et al, 2000Tiede et al, 2004]. ML II patients are characterized by dwarfism, skeletal abnormalities, developmental delay and cardiomegaly leading to death between 5 and 8 years of age [Kornfeld and Sly, 2001;Spranger et al, 2002].…”
Section: Introductionmentioning
confidence: 99%